AN ANALYSIS OF THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION : CASE STUDY OF MICRO ENTERPRISES AT VARIOUS CHIPS INDUSTRY ‘’ARTO MORO’’, AMPEL, BOYOLALI - UNNA RIA SAFITRI; A. FIDHDIARR ARIESTANTO TNK; PURWANTI (CV KULTURA DIGITAL MEDIA, 2021)
In this study the quality of service includes direct evidence, reliability, responsiveness, assurance and empathy. This study will look at the effect of simultaneous and partial service quality on customer satisfaction. The data collection techniques used are questionnaires, interviews, observations and documentation conducted from May to July 2018. Sampling techniques used incidentally, all data are analyzed with percentage analysis, multiple linear regression analysis, determination coefficient, F test and t test. The number of samples in this study was 100 respondents. From hypothesis testing it is known that the skin of the service simultaneously positively affects the customer satisfaction of Aneka Kripik